Charged-particle production as a function of multiplicity and transverse spherocity in pp collisions at √s = 5.02 and 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2019)
We present a study of the inclusive charged-particle transverse momentum (pTpTp_{\mathrm{T}}) spectra as a function of charged-particle multiplicity density at mid-pseudorapidity, dNch/dηdNch/dη\mathrm{d}N_{\mathrm{ch}}/\mathrm{d}\eta , in pp collisions at s√=5.02s=5.02\sqrt{s}=5.02 and 13 TeV covering the kinematic range |η|<0.8|η|<0.8|\eta |<0.8 and 0.15<pT<200.15<pT<200.15<p_{\mathrm{T}} <20 GeV/c. The results are presented for events with at least one charged particle in |η|<1|η|<1|\eta |<1 (INEL>0>0\,>0). The pTpTp_\mathrm{T} spectra are reported for two multiplicity estimators covering different pseudorapidity regions. The pTpTp_{\mathrm{T}} spectra normalized to that for INEL>0>0\,>0 show little energy dependence. Moreover, the high-pTpTp_{\mathrm{T}} yields of charged particles increase faster than the charged-particle multiplicity density. The average pTpT{ p}_{\mathrm{T}} as a function of multiplicity and transverse spherocity is reported for pp collisions at s√=13s=13\sqrt{s}=13 TeV. For low- (high-) spherocity events, corresponding to jet-like (isotropic) events, the average pTpTp_\mathrm{T} is higher (smaller) than that measured in INEL>0>0\,>0 pp collisions. Within uncertainties, the functional form of ⟨pT⟩(Nch)⟨pT⟩(Nch)\langle p_{\mathrm{T}} \rangle (N_{\mathrm{ch}}) is not affected by the spherocity selection. While EPOS LHC gives a good description of many features of data, PYTHIA overestimates the average pTpTp_{\mathrm{T}} in jet-like events.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 09.12.2019
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, Y. Yuncu [und 1101 weitere]